Auto-ethnography - Sikes, Patricia J. (Sage benchmarks in social research methods, 2013)
"From the 1980s onwards, there has been what has frequently been described as an auto/biographical turn in the social sciences and also in the arts and humanities. Changes in conceptions of self, society and identity, post-modern, post-structural and post-colonial influences and sensibilities to name but a few have all played their part in focusing attention on to, and valorising the perceptions and experiences of the individual...this new four-volume set seeks to capture the important articles that have come out of the field over the past decades. Framed by a newly-written introductory chapter, the collection includes work that spans disciplinary boundaries, bringing together a comprehensive resource"--Publisher.